Why do banks demand excess liquidity? : the case of Guyana - Khemraj, Tarron ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2007)
Examines why commercial banks demand excess liquidity in a small open economy, Guyana, which has undergone significant financial reforms after 1988.